Male sexual dysfunction after rectal cancer surgery: Results of a randomized trial comparing mesorectal excision with and without lateral lymph node dissection for patients with lower rectal cancer: Japan Clinical Oncology Group Study JCOG0212. Issue 12 (December 2016) - Saito, S.; Fujita, S.; Mizusawa, J.; Kanemitsu, Y.; Saito, N.; Kinugasa, Y.; Akazai, Y.; Ota, M.; Ohue, M.; Komori, K.; Shiozawa, M.; Yamaguchi, T.; et al.
Abstract: Background: We conducted a randomized controlled trial (JCOG0212) to determine whether the outcome of mesorectal excision (ME) alone for rectal cancer is not inferior to that of ME with lateral lymph node dissection (LLND). The present study focused on male sexual dysfunction after surgery. Methodology: Eligibility criteria included clinical stage II/III rectal cancer, the lower margin of the lesion below the peritoneal reflection, the absence of lateral pelvic lymph node enlargement, and no preoperative radiotherapy. After confirmation of R0 resection by ME, patients were intraoperatively randomized. Questionnaires using the International Index of Erectile Function (IIEF-5) about the sexual function of men were collected before and 1 year after surgery. Sexual dysfunction incidence was defined as the ratio of patients showing sexual dysfunction after surgery relative to the number who had no erectile dysfunction before surgery. Results: Among 701 patients enrolled between June 2003 and August 2010, 472 males were included. Among them, 343 (73%) completed preoperative and postoperative questionnaires. According to the study protocol, the incidences of sexual dysfunction in patients who underwent ME alone and ME with LLND were 68% (17/25; 95%CI, 47–85%) and 79% (23/29; 95%CI, 60–92%), respectively (p = 0.37). Incidences of sexual dysfunction in patients with no or only mild erectile dysfunction before surgery who underwent ME alone and ME with LLND were 59% (48/81) and 71% (67/95), respectively (p = 0.15). Multivariate analysis identified age as the only risk factor for sexual dysfunction after surgery (p = 0.02). Conclusions: LLND may not increase sexual dysfunction incidence after rectal cancer surgery. This incidence is associated with increased age. This trial is registered withClinicalTrials.gov, numberNCT00190541 and University Hospital Medical Information Network Clinical Trials Registry, number C000000034.